The Role of Transformational Leadership in Driving Digital Transformation - Meilani Hartono (Journal of Loomingulisus ja Innovatsioon, 2026)
Digital transformation has become essential for organizations seeking to stay competitive in an increasingly technology-driven world. As organizations strive to implement new technologies and business models, effective leadership plays a critical role in ensuring the success of these initiatives. This study explores the role of transformational leadership in driving digital transformation, focusing on how transformational leaders influence the adoption of digital technologies and the organizational changes required for successful transformation. The objective of this research is to examine the impact of transformational leadership on digital transformation outcomes, such as employee engagement, technology adoption, and operational efficiency. A mixed-methods approach was used, combining quantitative surveys and qualitative interviews with 200 employees and managers from various sectors, including technology, manufacturing, and finance. The findings reveal a strong positive correlation between transformational leadership and the success of digital transformation, with transformational leaders fostering a culture of innovation, engagement, and adaptability. Employees working under transformational leaders reported higher levels of motivation and willingness to embrace digital tools, leading to improved organizational performance. The study concludes that transformational leadership is crucial for driving digital transformation, and organizations should prioritize developing transformational leaders to navigate the challenges of digital change successfully.